2014
DOI: 10.1063/1.4904457
|View full text |Cite
|
Sign up to set email alerts
|

Influence of in-plane and bridging oxygen vacancies of SnO2 nanostructures on CH4 sensing at low operating temperatures

Abstract: Role of 'O' defects in sensing pollutant with nanostructured SnO 2 is not well understood, especially at low temperatures. SnO 2 nanoparticles were grown by soft chemistry route followed by subsequent annealing treatment under specific conditions. Nanowires were grown by chemical vapor deposition technique. A systematic photoluminescence (PL) investigation of 'O' defects in SnO 2 nanostructures revealed a strong correlation between shallow donors created by the in-plane and the bridging 'O' vacancies and gas s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 18 publications
3
66
0
Order By: Relevance
“…SnO 2 NPs were synthesized by annealing pristine quantum dots of size 2.4 nm at 300 and 800 °C in horizontal quartz tube furnace in the presence of air atmosphere for 1 h. The pristine sample was synthesized by soft chemical method, and a detailed synthesis and characterization of these NPs was reported elsewhere . Morphological studies of the synthesized materials were performed by high resolution transmission electron microscopy (HRTEM; Zeiss Libra 200) and field emission scanning electron microscopy (FESEM; Zeiss SUPRA 55) for samples annealed at different temperatures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SnO 2 NPs were synthesized by annealing pristine quantum dots of size 2.4 nm at 300 and 800 °C in horizontal quartz tube furnace in the presence of air atmosphere for 1 h. The pristine sample was synthesized by soft chemical method, and a detailed synthesis and characterization of these NPs was reported elsewhere . Morphological studies of the synthesized materials were performed by high resolution transmission electron microscopy (HRTEM; Zeiss Libra 200) and field emission scanning electron microscopy (FESEM; Zeiss SUPRA 55) for samples annealed at different temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…SnO 2 is an n ‐type wide band gap semiconductor with direct band gap of 3.6 eV. It is widely used as gas sensor, transparent conductors (when doped suitably), solar cells, Li‐ion batteries and also as a catalyst . The surface chemistry of a SnO 2 structures is a crucial parameter in all these applications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However for an effective use of QDs, it is very important to understand their distinct physical and chemical properties with respect to their bulk counterparts. Wide band gap n-type semiconducting SnO 2 nanostructures are well established for the use in technologically important applications like gas sensing, transparent electrodes, and as a catalyst [1][2][3][4]. It is also found that the SnO 2 is a potential material for much needed applications like solar cells [1,5,6], as anode materials in Li-ion battery [1,[7][8][9], and electrochemical supercapacitors [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Bonu et al. found the in‐plane OVs in SnO 2 played an important role in methane detection in the light of the photoluminescence measurements results . To the best of our knowledge, SnO 2 nanocrystals with abundant OVs are generally used to enhance the sensing performances of NO 2 and CH 4 , but the detection of TEA in this type gas sensor are rarely reported.…”
Section: Introductionmentioning
confidence: 99%